Equinodermos del Cabo de la Vela (La Guajira, Colombia) en la colección de referencia de la Universidad El Bosque (2016)
The echinoderms present in the reference collection of the Museum of Sciences University El Bosque were collected during various field trips by students of Biology program at Cabo de la Vela between 2005 and 2010. The specimens were reviewed and identified using different keys and taxonomic guides and confirmed by specialists. A total of 107 specimens, distributed in 9 orders, 11 families 12 genus and 17 species was obtained.